Self-Forgiveness and Self-Condemnation in the Context of Addictive Behavior and Suicidal Behavior - Webb JR; Boye CM (Dove Medical Press, 2024)
Jon R Webb, Comfort M Boye Department of Community, Family, and Addiction Sciences; Texas Tech University, Lubbock, TX, USACorrespondence: Jon R Webb, Texas Tech University, Department of Community, Family, and Addiction Sciences, 1301 Akron Avenue, Room 271, Lubbock, TX, 79409, USA, Tel +1 806 834 2265, Fax +1 806 742 0053, Email jon.r.webb@ttu.eduAbstract: Addictive behavior and suicidal behavior are serious individual- and public-level health concerns. For those struggling with either or both, self-condemnation is a common experience, especially with respect to shame, guilt, and self-stigma. Self-forgiveness, a construct common to both religiousness/spirituality and positive psychology, may be an effective tool in addressing the self-condemnation inherent to those struggling with addictive behavior and suicidal behavior. In this review paper, we discuss (1) the nature and definition of forgiveness, (2) theoretical modeling developed regarding the general association of forgiveness with health, (3) theoretical modeling developed regarding the specific association of forgiveness with better outcomes related to addictive and/or suicidal behavior, (4) the relevance of shame, guilt, and self-stigma to the development and maintenance of addictive and suicidal behavior, and (5) the role of self-forgiveness in addressing self-condemnation, especially shame, guilt, and self-stigma. Little work explicitly focused on the association of self-forgiveness with shame, guilt, and/or self-stigma has been done. However, empirical evidence is accumulating in support of other associations proposed in the Forgiveness-Addiction-Recovery Association (FARA) Model described herein. As such, it is likely that similar support will be found when the focus is deliberately turned to shame, guilt, and self-stigma.Keywords: positive psychology, shame, guilt, self-stigma, twelve-step model